Green Dakwah: The Transformation of Mosques as Agents of Nature Conservation in the Digital Age - Al kahfi, Al kahfi; Qonitah, Mona (Abdurrauf Journal of Islamic Studies, 2025)
The global environmental crisis increasingly demands the involvement of all sectors, including religious institutions. However, the role of mosques as agents of environmental da'wah in Indonesia remains underutilized, especially amid urbanization and low ecological literacy among Muslim communities. This study aims to examine and design mosque-based environmental da'wah programs as an integrative effort between Islamic values and ecological awareness. This research employs a qualitative approach using library research methods, analyzing classical and contemporary Islamic literature, public policy documents, and case studies of environmental da'wah practices in selected mosques. The findings reveal that mosques hold strategic potential as centers for ecological education through spiritual, educational, and participatory approaches. The proposed da'wah programs include thematic environmental sermons, educational mosque gardens, Friday clean-up movements, congregational waste banks, and training for environmentally conscious mosque administrators, supported by digital media outreach. These initiatives align with the Ministry of Religious Affairs' policy to mainstream environmental issues into religious activities. Environmental da'wah has proven effective in enhancing ecological spirituality, encouraging active community participation, and fostering socio-economic empowerment through mosque-based initiatives. [Krisis lingkungan global yang semakin mengkhawatirkan menuntut keterlibatan berbagai pihak, termasuk lembaga keagamaan. Namun, pemanfaatan masjid sebagai agen dakwah lingkungan di Indonesia masih belum optimal, terutama dalam konteks urbanisasi dan rendahnya literasi ekologi masyarakat Muslim. Penelitian ini bertujuan untuk mengkaji dan merancang program dakwah lingkungan berbasis masjid sebagai upaya integratif antara nilai-nilai Islam dan kesadaran ekologis. Metode yang digunakan adalah pendekatan kualitatif dengan studi pustaka, melalui telaah literatur klasik dan kontemporer, kebijakan publik, serta studi kasus praktik dakwah lingkungan di sejumlah masjid. Hasil penelitian menunjukkan bahwa masjid memiliki potensi strategis sebagai pusat edukasi ekologis melalui pendekatan spiritual, edukatif, dan partisipatif. Program dakwah lingkungan yang dikembangkan mencakup khutbah tematik lingkungan, taman edukatif, gerakan Jumat bersih, bank sampah jamaah, serta pelatihan pengurus masjid yang ramah lingkungan dengan dukungan media digital. Program ini sejalan dengan kebijakan Kementerian Agama RI dalam mengarusutamakan isu pelestarian lingkungan ke dalam aktivitas keagamaan. Dakwah lingkungan terbukti mampu meningkatkan spiritualitas ekologis, partisipasi aktif jamaah, serta memberdayakan masyarakat secara sosial dan ekonomi berbasis komunitas masjid.]